2010
DOI: 10.5194/acpd-10-1939-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aerosol-induced changes of convective cloud anvils produce strong climate warming

Abstract: Abstract. The effect of aerosol on clouds poses one of the largest uncertainties in estimating the anthropogenic contribution to climate change. In contrast, even small human-induced perturbations in cloud coverage, lifetime, height or optical properties can change the instantaneous radiative energy flux by hundreds of watts per unit area, and this forcing can be either warming or cooling. Clouds and aerosols form a complex coupled system that, unlike greenhouse gases, have relatively short lifetime (hours to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 27 publications
5
38
0
Order By: Relevance
“…Furthermore, convective anvils, which may have a large impact on the radiative balance, are not resolved in this study. Cloud invigoration over the Atlantic and Pacific Oceans has been observed to result in an increase in the total and anvil cloud fraction, a decrease in the tower size to anvil size ratio, and consequently an increase in the TOA downward irradiance [Koren et al, 2010b]. However, the majority of clouds that form in this region and season are shallow cumuli that do not contain anvils.…”
Section: Aerosol-cloud Relationships Determined From Simulations W/ Bsupporting
confidence: 90%
“…Furthermore, convective anvils, which may have a large impact on the radiative balance, are not resolved in this study. Cloud invigoration over the Atlantic and Pacific Oceans has been observed to result in an increase in the total and anvil cloud fraction, a decrease in the tower size to anvil size ratio, and consequently an increase in the TOA downward irradiance [Koren et al, 2010b]. However, the majority of clouds that form in this region and season are shallow cumuli that do not contain anvils.…”
Section: Aerosol-cloud Relationships Determined From Simulations W/ Bsupporting
confidence: 90%
“…The near-shore areas closer to the Asian continent experience larger increase of AOD compared to the remote maritime areas, and the consequent zonal extension of AOD enhancement just reflects the transportation process of particulate pollution from East Asia to West Pacific. Averaged over the analysis region, AOD is elevated by 0.03 in PD case, which accounts for 46% relative increase defined as the ratio of mean difference between PD and PI over the aerosols are consistent with the previous reports from satellite measurements [Koren et al, 2010] and CRM simulation results [Fan et al, 2012]. The response of the surface precipitation to the different aerosol scenarios is not uniform over the NW Pacific region (Figure 5.19g).…”
Section: Analysis Of Simulation Resultssupporting
confidence: 88%
“…Since convective transport may affect aerosols and hydrometeors in the upper troposphere, these changes in convective strength could significantly alter cloud anvil properties and WVC in the TTL. A recent study by Koren et al (2010) found that aerosol-induced invigoration of convection resulted in expanded anvil spatial coverage and reduced optical depth. Satellite analysis indicates that aerosols from forest fires result in smaller particles and much longer anvil lifetime (Lindsey and Fromm 2008) and biomass burning aerosols increase water vapor entering the stratosphere by decreasing ice particle size (Sherwood 2002).…”
Section: Introductionmentioning
confidence: 99%